Exploring English Teachers' Perception of the Ruang GTK Platform Implementation in Senior High Schools in Palopo - Lestari Yanti; Sahraini; Magfirah Thayyib (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study explores English teachers’ perceptions of the implementation of the Ruang Guru dan Tenaga Kependidikan (Ruang GTK) at SMAN 2 Palopo and SMKN 1 Palopo. As a transformation of PMM, Ruang GTK aims to facilitate teacher professional development, support performance management, and promote innovative teaching aligned with the Merdeka Curriculum. Employing a qualitative descriptive method, the data were collected through interviews, classroom observations, and document analysis involving twelve English teachers. The results indicate that most participants expressed favorable views toward the platform, particularly valuing its ease of access, the practicality of self-directed learning modules such as Pelatihan Mandiri, Diklat, Komunitas, Inspirasi Pembelajaran dan Dokumen Rujukan. These features improved teaching and learning quality. Nevertheless, several underutilized features of the Ruang GTK platform such as Perangkat Ajar, Refleksi Kompetensi, and Sertifikasi Pendidik present key challenges related to relevance, accessibility, and functionality. Teachers noted that the content lacks contextualization for vocational education, some features remain inaccessible, and others offer limited value for non-PPG users. The findings underscore the need for further refinement of the platform to ensure its effectiveness across diverse teaching contexts. This study offers insights into technology-based professional development and highlights the relevance of constructivist learning theory in teaching practice.